Burial and memorial in late antiquity: volume 1: Thematic perspectives - Lavan, Luke (Late Antique Archaeology Series, 2024)
This book presents current work on the archaeology of burial and memorial in late antiquity, with insights from excavation, science, and texts, from DNA to perfume traces, mausolea to relic translation, tomb robbing to statue spoliation, in East and West.